2019
DOI: 10.1159/000497478
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of ASCO and TOAST Classification System in Chinese Minor Stroke Patients

Abstract: Background: Precise subtype classification based on underlying pathophysiology is important to prevent recurrent attack in minor stroke patients. A newly developed Atherosclerosis, Small vessel disease, Cardiac source, Others (ASCO) phenotypic classification system aims to characterize patients using different grades of evidence for stroke subtypes. However, this system has not been specifically applied to minor stroke population. In our study, the impact of using the newer ASCO criteria on minor stroke etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Small artery occlusion (SAO) is one of the ischemic stroke subtypes categorized by the Trial of ORG10172 in Acute Stroke Treatment (TOAST) 7 . Previous study reported that in developing countries, SAO accounting for 16–22% of ischemic stroke cases, the percentage higher 4% than developed countries; 8 however, the latest research showed that SAO accounts for 27.3% of ischemic stroke cases in China, higher than the world level 9 . It is crucial to identify the different potential underlying causes of stroke subtype to targeted treatment and decrease the burden of stroke in China.…”
Section: Introductionmentioning
confidence: 89%
“…Small artery occlusion (SAO) is one of the ischemic stroke subtypes categorized by the Trial of ORG10172 in Acute Stroke Treatment (TOAST) 7 . Previous study reported that in developing countries, SAO accounting for 16–22% of ischemic stroke cases, the percentage higher 4% than developed countries; 8 however, the latest research showed that SAO accounts for 27.3% of ischemic stroke cases in China, higher than the world level 9 . It is crucial to identify the different potential underlying causes of stroke subtype to targeted treatment and decrease the burden of stroke in China.…”
Section: Introductionmentioning
confidence: 89%
“…The neurologic status at the time of CT was classified as symptomatic or asymptomatic according to the neurologic assessment documented in the clinical chart review using the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. 19,20 The maximum timing between events and imaging to consider a subject as symptomatic was 1 week. In the case of >1 week between ischemic symptoms and CTA of carotid arteries, the patient was excluded.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…The significant difference between intra-cardiac thrombi detection rates in these two cohorts may be attributed to the different prevalence of atherosclerosis, being the most common IS subtype in China. 26,27 LA/LAA thrombi detection: CCTA was shown to be an accurate and reliable alternative to TEE for the detection of LA/LAA thrombi in patients with AF, avoiding the discomfort and risks associated with TEE. 28 Compared to TEE as the gold standard for LA/LAA thrombi detection, mean sensitivity and specificity of CCTA are 96% and 92% respectively, and in some prospective single-center studies, have reached 100% and 99% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The significant difference between intra-cardiac thrombi detection rates in these two cohorts may be attributed to the different prevalence of atherosclerosis, being the most common IS subtype in China. 26,27…”
Section: Discussionmentioning
confidence: 99%